IMPROVING THE DEBATE ABILITY THROUGH INQUIRY METHOD AND AUDIO VISUAL LEARNING MEDIA IN COURSE OF SPEAKING SKILL (Lesson Study Results) - Prima Gusti Yanti (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2018)
AbstractThis study aims to apply the model of professional development of lesson study in Speech Skills course through debating ability of student of lndonesian language and literature study program of Faculty of Teacher Training and Education of Muhammadiyah University Professor Dr. Hamka. This lesson study program involves various elements, namely the lecturers team of lesson study, lecturers of speech skills students and semester III students of Indonesian Language and Literature Studies Program FKIP UHAMKA. This research uses Classroom Action Research which consists of (1) Plan stage, is development of teaching materials that is debate. (2) Do stage in the form of activities or implementation in the classroom by the model lecturer in the form of learning to students of the third semester, and (3) See stage or joint reflection between the model lecturer and the observer team about the advantages and disadvantages of teaching materials and processes that have been implemented. Lesson Study activities are designed in two cycles, each cycle consists of 2X meetings, at each meeting will be Plan, Do, and See stages in each learning process. The purpose of phasing in each cycle is to improve the students 'ability to speak which was previously passive, but continuously improved by using appropriate methods and media can improve students' ability in expressing their arguments so that students can improve their ability to argue. The results of this study indicate that: (1) the implementation of lesson study has given satisfaction to lecturer model and observer and student. (2) the are able to produce lessons (RPS, LKM, teaching materials, learning media, and quality assessment instruments) as they are made together with model lecturers and lecturers observer teams) (3) Dean of FKIP Uhamka’s support and its staff on lesson study activities for the improvement of lecturers professionalism that will ultimately improve the quality of education.Keywords: Ability, Inquiry, Media, Speech Skills